Berpikir Kritis Dan Kolaboratif Siswa SMK Ketintang Surabaya Pada Bidang Sensor dan Aktuator - Baskoro, Farid; Asto, I Gusti Putu; Kartini, Unit Three; Ibrohim, Ibrohim (Abimanyu : Jornal of Community Engagement, 2023)
This research is a Program community service (PKM) activity aimed at presenting an analysis of critical thinking and collaborative abilities among students of SMK Ketintang in the field of sensors and actuators. This PKM involves a trial of critical thinking skills through a series of multiple-choice questions related to sensors and actuators. Additionally, an evaluation of collaborative abilities is conducted using a questionnaire, where participants provide feedback on teamwork, contributions, and interactions within their respective groups. The results of this PKM show that the majority of students demonstrated good performance in interpretation, analysis, and evaluation, with positive percentages ranging from 57% to 66%. This indicates a strong ability to comprehend and analyze information related to sensors and actuators. Meanwhile, the evaluation of collaborative abilities showed positive responses from the participants, with high scores in teamwork, contributions, and interactions. These results indicate the existence of effective teamwork that can help students solve a problem. Keywords: Critical, Collaborative, Education